2019
DOI: 10.1105/tpc.18.00916
|View full text |Cite|
|
Sign up to set email alerts
|

The Cytochrome b6f Complex Is Not Involved in Cyanobacterial State Transitions

Abstract: Photosynthetic organisms must sense and respond to fluctuating environmental conditions in order to perform efficient photosynthesis and to avoid the formation of dangerous reactive oxygen species. The excitation energy arriving at each photosystem permanently changes due to variations in the intensity and spectral properties of the absorbed light. Cyanobacteria, like plants and algae, have developed a mechanism, named "state transitions," that balances photosystem activities. Here, we characterize the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 99 publications
(129 reference statements)
0
29
0
Order By: Relevance
“…2), suggesting that changes in both PBS and Chl-containing-complexes are involved in state transitions. 51,52 It has been observed that PSII-related fluorescence is lower in State II compared to that in State I (see Tables 1 and 2). However, only one third of the realized studies showed that PSI-related fluorescence is lower in State I com- .…”
Section: Following Photosystem Fluorescence Changes During State Tranmentioning
confidence: 97%
See 2 more Smart Citations
“…2), suggesting that changes in both PBS and Chl-containing-complexes are involved in state transitions. 51,52 It has been observed that PSII-related fluorescence is lower in State II compared to that in State I (see Tables 1 and 2). However, only one third of the realized studies showed that PSI-related fluorescence is lower in State I com- .…”
Section: Following Photosystem Fluorescence Changes During State Tranmentioning
confidence: 97%
“…69,70 However, due to differences in this redox state balance between cyanobacterial strains, the level of PQ reduction state varies, leading to different levels of State II fluorescence in the dark. 52,72 Mutants in the respiratory process also affect state transitions. For instance, NDH-1 and SDH mutants are in State I in the dark, [73][74][75][76] while terminal oxidase mutants have a more pronounced dark State II.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Cyanobacteria allocate most of their chlorophyll a to photosystem I (PSI), whereas PBS are mostly coupled to photosystem II (PSII) (e.g., Myers et al 1980, Luimstra et al 2018. It has been hypothesized that PBS can dynamically move back and forth between PSII and PSI by state transitions (Mullineaux et al 1997, van Thor et al 1998), but recent research does not fully support this hypothesis (Chukhutsina et al 2015, Ranjbar Choubeh et al 2018, Calzadilla et al 2019. By contrast, the cyanobacterium Prochlorococcus, green algae, and many other eukaryotic phytoplankton (e.g., diatoms, coccolithophores, and dinoflagellates) lack PBS, but contain light-harvesting complexes consisting of chlorophylls and carotenoids that can effectively transfer light energy to both photosystems (Chisholm et al 1992, Natali and Croce 2015, Nawrocki et al 2016; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While much is known about state transitions in plants, how they evolved is unclear, in part due to our poor understanding of this process in cyanobacteria, the first oxygen-evolving photosynthetic organisms. Calzadilla et al (2019) recently discovered that, surprisingly, state transitions in the model cyanobacteria Synechocystis PCC 6803 and Synechococcus elongatus occur in a manner quite different from that of plants and green algae. First, a process in PSII associated with fluorescence quenching independent of PSI plays an important role in cyanobacterial state transitions.…”
mentioning
confidence: 99%